PENGUATAN KAPASITAS KEMAMPUAN ORANG TUA MENGAJARKAN SPEAKING KEPADA ANAK-ANAK DI LKM NUSANTARA - Sri Endah Kusmartini (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The members of LKM Nusantara have conducted many things to create a prosperous and dignified society. In the field of education, the members of LKM Nusantara assisted by the lecturer of State Polytechnic of Sriwijaya who conducted the community service strived to strengthen the capacity of parent’s ability to teach speaking to the kids. The activity was very urgent because they believe that English was important for everybody in the global era; there was no instant process to reach the goal; and also the learning process should start from the very beginning. The activity was also very urgent due to the lack of abilities of the partners to teach speaking to the kids; limited access for the elementary school students to practice speaking; and also because of economic insecurity that they cannot finance the children to take English courses or training. The methods used in this activity were the participatory method and the method of mentoring which were carried out in an integrated manner at each stage of the activity. The positive impact can be seen after the training and mentoring were conducted; the ability of partners improved in teaching speaking to the children at home and they were able to teach speaking in a flexible, fun, and energetic manner.